MxA interacts with and is modified by the SUMOylation machinery - Brantis-de-Carvalho, Carlos Eduardo [UNESP]; Maarifi, Ghizlane; Gonçalves Boldrin, Paulo Eduardo [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Nisole, Sebastien; Chelbi-Alix, Mounira K.; Valentini, Sandro Roberto [UNESP] (Elsevier B.V., 2015)
Mx proteins are evolutionarily conserved dynamin-like large GTPases involved in viral resistance triggered by types I and III interferons. The human MxA is a cytoplasmic protein that confers resistance to a large number of viruses. The MxA protein is also known to self-assembly into high molecular weight homo-oligomers. Using a yeast two-hybrid screen, we identified 27 MxA binding partners, some of which are related to the SUMOylation machinery. The interaction of MxA with Small-Ubiquitin MOdifier 1 (SUMO1) and Ubiquitin conjugating enzyme 9 (Ubc9) was confirmed by co-immunoprecipitation and co-localization by confocal microscopy. We identified one SUMO conjugation site at lysine 48 and two putative SUMO interacting motifs (SIMa and SIMb). We showed that MxA interacts with the EIL loop of SUMO1 in a SIM-independent manner via its CID-GED domain. The yeast two-hybrid mapping also revealed that Ubc9 binds to the MxA GTPase domain. Mutation in the putative SIMa and SIMb, which are located in the GTPase binding domain, reduced MxA antiviral activity. In addition, we showed that MxA can be conjugated to SUMO2 or SUMO3 at lysine 48 and that the SUMOylation-deficient mutant of MxA (MxA(K48R)) retained its capacity to oligomerize and to inhibit Vesicular Stomatitis Virus (VSV) and Influenza A Virus replication, suggesting that MxA SUMOylation is not essential for its antiviral activity. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: MX1; MxA; Yeast two-hybrid; SUMOylation; EIL loop; SUMO; Ubc9 and antiviral activity